2020
DOI: 10.1177/1088767920928106
|View full text |Cite
|
Sign up to set email alerts
|

Murder as Importation: An Empirical Study of the Continuity of Homicide Offending From Community to Confinement

Abstract: Prison murder is the most severe form of institutional violence but its exceedingly low prevalence has limited prior research. Recent studies of prison murders make clear that serious, violent, and chronic career criminals are most likely to perpetrate inmate murders with equivocal evidence of the role of prior homicide offending on prison murder. Using retrospective administrative data from 1,005 prisoners selected from the southwestern United States, the current study examined whether homicide offending in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
2
2
0
1
Order By: Relevance
“…More recent penological studies have employed advanced statistical techniques, such as latent class and profile analyses, that can identify unobserved groupings among prisoner samples (Cihan et al, 2017a, b; Morris et al, 2012). Similar to earlier research, these studies document heterogeneity in institutional adjustment with evidence of a small group of prisoners committing the most violence and rule violations, and these individuals tend to have extensive criminal and violence histories prior to confinement (also see DeLisi & Butler, 2020; Reidy & Sorensen, 2017; Reidy et al, 2020; Schenk & Fremouw, 2012; Trulson, 2007). Consistent with the importation model, continued involvement in violent assaults and other disruptive conduct also mostly predicts punitive institutional responses such as administrative segregation and disciplinary segregation (Logan et al, 2017; Trulson & Marquart, 2010).…”
Section: Maladaptive Behavior In Prisonsupporting
confidence: 75%
“…More recent penological studies have employed advanced statistical techniques, such as latent class and profile analyses, that can identify unobserved groupings among prisoner samples (Cihan et al, 2017a, b; Morris et al, 2012). Similar to earlier research, these studies document heterogeneity in institutional adjustment with evidence of a small group of prisoners committing the most violence and rule violations, and these individuals tend to have extensive criminal and violence histories prior to confinement (also see DeLisi & Butler, 2020; Reidy & Sorensen, 2017; Reidy et al, 2020; Schenk & Fremouw, 2012; Trulson, 2007). Consistent with the importation model, continued involvement in violent assaults and other disruptive conduct also mostly predicts punitive institutional responses such as administrative segregation and disciplinary segregation (Logan et al, 2017; Trulson & Marquart, 2010).…”
Section: Maladaptive Behavior In Prisonsupporting
confidence: 75%
“…Finally, recent work by Logan et al (2021) noted that veterans scoring higher on the Level of Service Inventory-Revised (LSI-R) were at an increased risk of institutional misconduct and that those with either TBI or PTSD were at greater risk of recidivating post-release, relative to those who had not been diagnosed. That these aforementioned pre-prison variables influence how inmates adapt to incarceration is congruent with the well-known importation theory of inmate adjustment (DeLisi & Butler, 2020; DeLisi et al, 2011; Mears et al, 2013). This theory is predicated on the idea that inmates “import” their past experiences and various sociodemographic characteristics that either assuage or exacerbate the pains of imprisonment (Harer & Steffensmeier, 1996; Irwin & Cressey, 1962).…”
supporting
confidence: 80%
“…As mentioned, a spate of research has indicated that incarcerated people import their social and criminal histories with them into prison such that their experiences during incarceration often mirror their experiences prior to admission (DeLisi et al, 2004, 2010, 2011). Recent scholarship has further demonstrated that serious, chronic offending prior to incarceration is tied to disproportionate levels of prison violence and misconduct (DeLisi & Butler, 2020; Logan, Long et al, 2022), which in turn corresponds with higher levels of victimization. Evidence of the potential victim–offender overlap among incarcerated veterans could also be attributed to differences in age and socioeconomic capital (e.g., educational attainment), both of which are reflected in MnSTARR scores.…”
Section: Discussionmentioning
confidence: 99%